PROCEDIMENTOS DOS ALUNOS ASSOCIADOS ÀS SUAS AÇÕES COGNITIVAS EM ATIVIDADES DE MODELAGEM MATEMÁTICA - CASTRO, ÉLIDA MAIARA VELOZO DE (2017)
In this research we use the Mathematical Modeling as a pedagogical alternative to approach problem situations of the reality and interest of the student and to improve the learning of Mathematics and other areas of knowledge. The objective of this study is to investigate what is revealed of students' cognitive actions in the development of mathematical modeling activities. The research was realized in two classes of eighth grade students from a public school in the state of Paraná. The methodological option adopted is based on the qualitative approach and counted on bibliographical studies on the Mathematical Modeling such as Almeida Silva and Vertuan (2013), Almeida e Silva (2012), Vertuan (2013), Veronez (2013), and others. For the data analysis we used audio and video recordings and the students' written statements. These data were collected during thirty classes, in which several mathematical modeling activities were developed, such as: Mate-herb, Maize and Planets of the Solar System. The results of the research point out that the process of searching for a solution to the problem, when the students involved themselves in mathematical modeling activities, requires them to mobilize and construct knowledge and this leads them to explain, modify and/or modify their ways of thinking and their decisions, reflections of their cognitive actions and manifested through procedures. These procedures, in addition to portraying students' mobilization/construction of knowledge, since they are related to their way of thinking, understanding and administering the information about the subject that originated this activity of mathematical modeling, indicate that there is no linearity in the actions of the students. Such mobilization provokes a process of comings and goings in relation to the aspects of the situation or problem studied, the mathematical objects and the answers recognized as solution, besides revealing that the procedures manifested by the students are complemented to the step that they seek to respond to the question that originated the mathematical modeling activity.